B Cell-Derived Extracellular Vesicles Reveal Residual B Cell Activity in Kidney Graft Recipients Undergoing Pre-Transplant Desensitization - Cucchiari, David; Tubita, Valeria; Rovira, Jordi; Ramirez-Bajo, Maria J.; Banon-Maneus, Elisenda; Lazo-Rodriguez, Marta; Hierro-Garcia, Natalia; Borràs, Francesc E.; Ventura-Aguiar, Pedro; Piñeiro, Gastón J.; Martorell, Jaume; Peri, Lluís; et al. (Frontiers in Medicine, 2021)
Background: Living-donor kidney transplant (LDKT) recipients undergoing desensitization for HLA-incompatibility have a high risk of developing antibody-mediated rejection (ABMR). The purpose of the study was to evaluate if residual B cells activity after desensitization could be estimated by the presence of circulating B cells-derived extracellular vesicles (BEVs). Methods: BEVs were isolated by sepharose-based size exclusion chromatography and defined as CD19+ and HLA-II+ extracellular vesicles. We analyzed stored serum samples from positive cross-match LDKT recipients before and after desensitization, at first post-transplant biopsy and at 12-month protocol biopsy (n=11). Control groups were formed by hypersensitized patients not submitted to desensitization (n=10) and low-risk recipients (n=9). A prospective validation cohort of 11 patients also included the analysis of B cells sub-populations in recipients’ blood and lymph nodes recovered upon graft implantation, as well as BEVs analysis before and after desensitization. Results: We found out that CD19+ and HLA-II+BEVs dropped significantly after desensitization and relapsed in patients who later developed ABMR. We validated these findings in a proof-of-concept prospective cohort of 6 patients who received the same desensitization protocol and a control group of 5 LDKT recipients. In these patients, B cells sub-populations were also studied in recipients’ blood and lymph nodes recovered before graft implantation. We confirmed the significant drop in BEVs after desensitization and that this parallels the reduction in CD19+cells in lymph nodes, while in peripheral blood B cells were almost undetectable. Conclusions: BEVs reflected B-cell residual activity after desensitization and this could be a valid surrogate of humoral alloreactivity in this setting.